Implementasi Model Pembelajaran Team Teaching untuk Meningkatkan Prestasi Belajar Siswa Bidang Studi Matematika Kelas VIII MTs. Nurul Huda Genteng Tahun Ajaran 2017-2018 - Nawal Ika Susanti (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
This research is a Class Action Research which aims to improve students' mathematics learning outcomes through the Teaching Teaching Learning model in class VIII MTs. Nurul Huda material Triangle. This research was conducted in 2 cycles, namely from each cycle consisting of 5 meetings and the last meeting was used for evaluation. During the implementation of the cycle, the team teaching learning model can be said to be quite successful because it can increase student activity and learning outcomes. An increase in activity and learning outcomes from the implementation of learning cycle I to cycle II is 6.11%.. So it can be concluded that student activities fall into the active category. As for student learning outcomes in the first cycle of 77.27% and 90.9% in cycle II, so that student learning outcomes experienced an increase of 13.63%. This shows that team teaching learning models can improve student activity and student learning outcomes. Based on the analysis of the results of tests I and II, one of the obstacles faced by students at the time of testing was the lack of students' understanding of the count operation on the triangle. Another factor is the inaccuracy of students in doing the tests given